2014
DOI: 10.1590/0101-60830004111520
|View full text |Cite
|
Sign up to set email alerts
|

Novel neurotherapeutics in psychiatry: use and rationale of transcranial direct current stimulation in major depressive disorder

Abstract: Background: Transcranial direct current stimulation (tDCS) is a novel non-pharmacological intervention being investigated for the treatment of major depressive disorder (MDD). Objective: To perform an updated review of tDCS for MDD. Method: Systematic review in Medline/PubMed and other databases of all clinical studies evaluating the clinical efficacy of tDCS in MDD, from the first date available to December/2013. Results: Out of 55 articles, 24 were included, being 6 open-label studies; 8 randomized, double-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…This bifrontal electrode montage is frequently used in treatment of clinically depressed patients (see Brunoni et al, 2013a,b;2014) aiming to augment (hypo)activity in the left hemisphere, as well as to restore the well known imbalance between both hemispheres in depression (Phillips et al, 2003). In fact, anodal tDCS over the left DLPFC is ubiquitously used in depression trials, whereas the cathode position varies between the right DLPFC, right supraorbital area and extracephalic positions (as reviewed by Moffa, Valiengo, Shiozawa, & Brunoni, 2014). For cognitive functioning, a review of the literature showed that most tDCS studies with a focus on working memory have placed the anodal electrode over a frontal scalp location (mostly F3), and the cathode over the controlateral supraorbital cortex (for a meta-analysis, see Brunoni & Vanderhasselt, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This bifrontal electrode montage is frequently used in treatment of clinically depressed patients (see Brunoni et al, 2013a,b;2014) aiming to augment (hypo)activity in the left hemisphere, as well as to restore the well known imbalance between both hemispheres in depression (Phillips et al, 2003). In fact, anodal tDCS over the left DLPFC is ubiquitously used in depression trials, whereas the cathode position varies between the right DLPFC, right supraorbital area and extracephalic positions (as reviewed by Moffa, Valiengo, Shiozawa, & Brunoni, 2014). For cognitive functioning, a review of the literature showed that most tDCS studies with a focus on working memory have placed the anodal electrode over a frontal scalp location (mostly F3), and the cathode over the controlateral supraorbital cortex (for a meta-analysis, see Brunoni & Vanderhasselt, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we could not test different montages as this protocol used participants recruited for a larger study. Nonetheless, these results are valid for, at least, this bifrontal montage that is commonly used in tDCS MDD studies [15]. Finally, the study sample was relatively small; therefore some analyses might be underpowered, particularly the lack of significant differences between patients and controls in the IST task at baseline and between type of stimulation in depressed patients in the n-back task.…”
Section: Discussionmentioning
confidence: 68%
“…The bifrontal tDCS montage that was already demonstrated to be an effective montage for the treatment of the acute depressive episode [15] was used, besides positive effects in emotional and non-emotional cognition in depressed patients after tDCS [2,16,24] For the non-emotional working memory task, we used the n-back task that assesses the short-term storage, selective and sustained attention, online manipulation of information in a mental workspace and is robustly associated with prefrontal cortex activation.N-back have been studied for several authors that related impairment of performance in MDD patients [5][17] (Diamond,2013). For the emotional working memory task we used the IST that evaluates the ability to update and shift between emotional representations in working memory [11].…”
Section: Introductionmentioning
confidence: 99%
“…As duas principais técnicas de estimulação cerebral não invasiva são a estimulação magnética transcraniana (EMT) e a estimulação por corrente contínua (ETCC). Ambas atingem diretamente as estruturas cerebrais, promovendo alterações plásticas de maneira focal, indolor e com largo limite de segurança 16,17 .…”
Section: Introductionunclassified